2018
DOI: 10.1155/2018/6565783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sterilisation Techniques for Regenerative Medicine Scaffolds Fabricated with Polyurethane Nonbiodegradable and Bioabsorbable Nanocomposite Materials

Abstract: An effective sterilisation technique that maintains structure integrity, mechanical properties, and biocompatibility is essential for the translation of new biomaterials to the clinical setting. We aimed to establish an effective sterilisation technique for a biodegradable (POSS-PCL) and nonbiodegradable (POSS-PCU) nanocomposite scaffold that maintains stem cell biocompatibility. Scaffolds were sterilised using 70% ethanol, ultraviolet radiation, bleach, antibiotic/antimycotic, ethylene oxide, gamma irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Since no new absorption peaks are visible in the spectra of the differently treated scaffolds, it can be concluded that no new chemical bond is formed between the growth factor or ascorbic acid and the polymer, even in the UV sterilized scaffolds, so the individual components were not chemically modified. In other studies, it was also observed that UV sterilization did not lead to visible changes in the FTIR spectra of other types of materials/scaffolds, like PLA 28 , polyurethanes 29 or PLGA 30 .
Figure 1FTIR and DSC characterization of differently stored and UV sterilized bioactive DP scaffolds. ( A ) FTIR absorbance spectra for bioactive DP scaffolds incorporating PDGF-BB or ascorbic acid, with or without UV sterilization.
…”
Section: Resultsmentioning
confidence: 80%
“…Since no new absorption peaks are visible in the spectra of the differently treated scaffolds, it can be concluded that no new chemical bond is formed between the growth factor or ascorbic acid and the polymer, even in the UV sterilized scaffolds, so the individual components were not chemically modified. In other studies, it was also observed that UV sterilization did not lead to visible changes in the FTIR spectra of other types of materials/scaffolds, like PLA 28 , polyurethanes 29 or PLGA 30 .
Figure 1FTIR and DSC characterization of differently stored and UV sterilized bioactive DP scaffolds. ( A ) FTIR absorbance spectra for bioactive DP scaffolds incorporating PDGF-BB or ascorbic acid, with or without UV sterilization.
…”
Section: Resultsmentioning
confidence: 80%
“…TE scaffolds should be free of contamination by living organisms such as bacteria and viruses for in vitro and in vivo tests and also for implantation to the human body. There are various methods used for this purpose, such as treatments with heat ( Fleith et al, 2005 ; Yoganarasimha et al, 2014 ), gamma irradiation ( Fleith et al, 2005 ), UV ( Andrews et al, 2007 ), plasma ( Poncin-Epaillard and Legeay, 2003 ; Griffin et al, 2018 ), ethylene oxide ( Andrews et al, 2007 ; Yoganarasimha et al, 2014 ), ethanol ( Griffin et al, 2018 ), and peracetic acid ( Yoganarasimha et al, 2014 ). As the efficiency of the methods in terms of the degree of removal/inactivation of microorganism varies, it might be appropriate to clarify the difference between the terms of disinfection and sterilisation.…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
“…One highly tested synthetic polymer for adipose regeneration is Poly(e-caprolactone) (PCL), a biocompatible and biodegradable FDA approved polymer for medical devices [3]. Our group have modified PCL with polyhedral oligomeric silsesquioxane (POSS) nanoparticles to improve its hydrophobicity and inertness to form a nanocomposite polymer called POSS-PCL [4][5][6][7]. We have shown that POSS-PCL can support cell adhesion, proliferation and differentiation acting as an effective scaffold to support cell survival [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Our group have modified PCL with polyhedral oligomeric silsesquioxane (POSS) nanoparticles to improve its hydrophobicity and inertness to form a nanocomposite polymer called POSS-PCL [4][5][6][7]. We have shown that POSS-PCL can support cell adhesion, proliferation and differentiation acting as an effective scaffold to support cell survival [4][5][6][7]. However, a successful biodegradable scaffold for adipose tissue engineering must integrate with the surrounding host tissue by integrating by laying down extracellular matrix and angiogenesis without causing an immune response or capsule formation to degrade effectively with time.…”
Section: Introductionmentioning
confidence: 99%